2015
DOI: 10.1097/npt.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Versus Continuous Walking on Distance Walked and Fatigue in Persons With Multiple Sclerosis

Abstract: Subjects with MS walked farther, and with less fatigue, when walking intermittently rather than continuously. Persons with MS may be able to tolerate a greater dose of walking training if the walking bouts are intermittent. Further study to determine the benefits of a walking exercise program using intermittent walking is recommended.Video Abstract available for additional insights from the authors (Supplemental Digital Content 1, http://links.lww.com/JNPT/A103).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Although other perceived fatigue measures were sometimes used (e.g., Fatigue Impact Scale, Multidimensional Fatigue Inventory, VAS) none were used more than twice across the 19 studies, which precluded any preliminary sensitivity analysis. Although some studies (23, 46, 47) also included measures of acute perceived fatigue, these values were dropped due to the low number of effects (k = 3). Because the sensitivity analysis found that the mean effect did not differ depending on the perceived fatigue measure, effects were averaged together when multiple perceived fatigue measures were used within the same study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although other perceived fatigue measures were sometimes used (e.g., Fatigue Impact Scale, Multidimensional Fatigue Inventory, VAS) none were used more than twice across the 19 studies, which precluded any preliminary sensitivity analysis. Although some studies (23, 46, 47) also included measures of acute perceived fatigue, these values were dropped due to the low number of effects (k = 3). Because the sensitivity analysis found that the mean effect did not differ depending on the perceived fatigue measure, effects were averaged together when multiple perceived fatigue measures were used within the same study.…”
Section: Resultsmentioning
confidence: 99%
“…Only three studies (23, 46, 47) measured perceived fatigue “right now”, and this low number prevented timing of fatigue assessment from being considered as a moderator. Perceived fatigue may be variable both within (55) and between (56) days in people with MS. Of the most common measures from studies included in this meta-analysis, the MFIS asks “how much of a problem fatigue has caused them during the past month, including the day of testing” (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6MWT is a frequently used measure of physical performance and endurance. 26 It has been previously modified in administration and scoring to assess physical fatigability in people with MS. 15,27,28 The version used in this study was used by Goldman et al 28 Specifically, instructions regarding permitted rest and encouragement phrases were eliminated and instructions regarding speed were emphasized. The administration was further modified for the present study by eliminating reminders every minute of how much time was remaining, and the participants were not informed that they would be walking for 6 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Therapists and clinicians may need to consider structuring their interventions to limit increasing MS-related fatigue. For example, Karpatkin et al 27 suggested that people with MS might exhibit less fatigue if they walk intermittently instead of continuously. This study showed that people with MS who walked intermittently for 6 minutes (ie, walked every 2 minutes and rested another 2 minutes) had less fatigue and walked longer distances compared with those who continuously walked for 6 minutes.…”
Section: Nfi-ms and Clinical Characteristicsmentioning
confidence: 99%